2014
DOI: 10.1016/j.jiph.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Dengue hemorrhagic fever: Comparison of patients with primary and secondary infections

Abstract: Primary dengue infection is frequently associated with DHF. Patients with DHF caused by secondary dengue infection have lower at admission platelet counts and higher ALT value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
5
27
0
2
Order By: Relevance
“…13,14 Present study also reports high frequency (79%) of secondary dengue cases. Although secondary dengue infection shown to be associated with more severe illness i.e DHF / DSS most probably due to antibody dependent enhancement, primary dengue infection has also been reported to be associated with DHF.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…13,14 Present study also reports high frequency (79%) of secondary dengue cases. Although secondary dengue infection shown to be associated with more severe illness i.e DHF / DSS most probably due to antibody dependent enhancement, primary dengue infection has also been reported to be associated with DHF.…”
Section: Resultssupporting
confidence: 66%
“…Dengue NS1 antigen and Dengue specific IgA antibody based assays have been shown to be useful during early febrile days. [5][6][7][8][9][10][11][12][13][14][15][16][17] ELISA and ICT based NS1 assay have been used as a diagnostic tool during febrile phase till defervescence (1 -9 days of fever onset) however, due to presence of virus -IgG immunocomplexs this assay has shown to be less sensitive in secondary infection as compared to primary infections 18,19 and may give false negative results in dengue endemic and hyperendemic areas. Studies comparing sensitives and specificities of IgA and NS1 reported dengue IgA to be more sensitive during early febrile phase of both primary and secondary dengue infection.…”
Section: -416mentioning
confidence: 99%
“…Exposure to one DENV serotype confers long-lived immunity against a homotypic secondary infection. However, secondary infection with a heterologous serotype of DENV is the major risk factor to induce severe DENV disease [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Secondary infection with different serotype may elicit antibody-dependent enhancement (ADE) response, which facilitates infection of Fc-receptor-bearing cells with DENV and amplified production of cytokines (78). These responses were reported to be linked to severe symptom and increased mortality (910). DHF or DSS have been not reported yet in Korea.…”
Section: Introductionmentioning
confidence: 99%